An Elegy of a Patriarch: Boys will be Boys by Sara Suleri - Nawaz, Muhammad (International Journal of English Literature and Social Sciences (IJELS), 2019)
Pakistani society is male dominant society and patriarchal values are rife there from her emergence. Sara Suleri’s father is a man of words and makes himself clear in firm and clear tone. Sara Suleri has tried to portray this scenario through her memoir Boys will be Boys. Though Sara touches the topics of politics, history and culture of Pakistan but main focus is circumstances in which concept of male gaze seems to be overloaded here. Norms of traditions prevalent in Pakistan always favor male member of society. Male gaze concept is one of the off-shoot of feminist ideology; where patriarchy, dominance and upper-hand are norms. Sara Suleri’s father is perfect example of patriarchy. He always tried to force his point of view on female family members.